Routine vaginal examination to assess labor progress at 8 compared to 4 h after early amniotomy following Foley balloon ripening in the labor induction of nulliparas: A randomized trial - C. M. Nashreen; Mukhri Hamdan; Jesrine Hong; Maherah Kamarudin; Rahmah Saaid; Peng Chiong Tan (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Our objective was to compare the performance of the first vaginal examination at 8 vs 4 h after amniotomy following Foley ripening in nulliparous labor induction. Material and Methods A randomized controlled trial was conducted from June 2021 to January 2022. 210 nulliparas at term for labor induction were randomized: 105 each to first vaginal examination at 8 or 4 h after Foley balloon ripening and amniotomy. Titrated oxytocin infusion was routinely commenced after amniotomy to expedite labor. Primary outcomes were the amniotomy‐to‐delivery interval (non‐inferiority hypothesis) and maternal satisfaction with their allocated labor care (superiority hypothesis) within 24 h after delivery. Analyses performed using t‐test, Mann–Whitney U test, and Chi‐squared test as appropriate. Results The amniotomy‐to‐delivery interval was mean ± standard deviation 8.7 ± 3.4 vs 8.4 ± 3.7, mean difference 0.4 (97.5% CI: −0.7 to 1.5) hours, p = 0.442 within the pre‐specified 2‐hour non‐inferiority margin, and maternal satisfaction score with allocated labor care was median [interquartile range] 8[7.5–10] vs 8[7.0–10], p = 0.248 for 8 vs 4 h arms, respectively. The amniotomy to first vaginal examination intervals was 5.9 ± 2.3 vs 3.6 ± 1.0 h, p < 0.001, and the number of vaginal examinations was 2[1–2.5] vs 3 [2, 3], p < 0.001 for 8 vs 4 h, respectively. The first vaginal examination was less likely to have been performed as scheduled, more likely to be indicated by the urge to bear down, and non‐reassuring cardiotocography for the 8 h arm (p < 0.001). Spontaneous vaginal delivery was significantly more likely and instrumental vaginal delivery less likely, but cesarean rate was not significantly different for the 8 h arm (p = 0.017). Conclusions A routine first vaginal examination at 8 h compared to 4 h is non‐inferior for the time to birth but does not increase maternal satisfaction although the number of vaginal examinations is fewer. The increase in spontaneous vaginal delivery and reduction in instrumental vaginal delivery rates warrant further powered primary evaluation.